Criminal law policy: Environmental pollution at Palembang port - Muhammad Zulchoir Rangkuti; Khalisah Hayatuddin; Erli Salia; Abdul Latif Mahfuz (The International Journal of Politics and Sociology Research, 2023)
This research examines the criminal law policy towards environmental pollution cases in Boom Baru Harbor and its surroundings in Palembang City, with a focus on Annex 5 Marine Pollution 73/78. This research aims to answer two main questions: 1) How is the criminal law policy towards environmental pollution cases based on Annex 5 Marine Pollution 73/78 at the Port of Boom Baru and its surroundings in Palembang City? 2) What are the factors that influence the application of the criminal law policy? The research method used is normative juridical research method using primary data and secondary data. The results showed that the current criminal law policy, such as UUPPLH No. 5 of 1978, has not been effective in handling cases of environmental pollution in the port. The relationship between UUPPLH No. 5 of 1978 and the provisions of UUPPLH No. 32 of 2009 Article 63 paragraph (2) letter a is still unclear. Some of the factors affecting the implementation of criminal law policy include problems in the law that are not clear enough, higher priority of law enforcers on other cases such as theft and murder, limited facilities including laboratory facilities and costs for involving expert witnesses, as well as a lack of legal awareness and public concern for the environment. This research provides an understanding of the challenges in implementing criminal law policies to protect the environment in the New Boom Port and its surroundings in Palembang City. Recommendations include expanding legal explanations, increasing public awareness, improving facilities, and expanding repressive measures in handling environmental pollution cases.